LINGUPOETICS OF SIMILARITIES IN SAIDA ZUNNUNOVA'S POEMS (Eureka Journal of Education & Learning Technologies, 2026)
This article examines the repetitions used in the poems of Saida Zunnunova and their specific features. The epithet (adjective) category is one of the most important stylistic means of the language, which helps to create richer and more colorful images through words.
Keywords: Epithet, compound epithet, phraseological epithet, descriptive epithet, evaluative epithet, emotional-psychological epithet.